Pelatihan Pengelolaan Stres dan Pola Asuh Dalam Upaya Pencegahan Stunting Pada Ibu PKK Di Dusun Kaliasin 1 - Putri Wulan Gustiani; Winda Primasari (ACADEMICS IN ACTION Journal of Community Empowerment, 2023)
Parenting is one of the factors that can cause stunting. Parenting has an important influence on the growth and development of a child. To provide good parenting, it must also be supported by good stress management. Stress is a problem experienced by everyone, and many negative things that can be caused by stress, especially not being able to provide good parenting for children. Therefore good parenting must coexist with good stress management as well. respondents in this service are parents, especially mothers who are members of the PKK organization. The implementation method used in this service is consultation to find out the problems that occur in the community, then psychoeducation to provide additional knowledge to the community in terms of parenting and stress management and finally relaxation technique training as an example of how to manage stress in a good way and can be done by respondents at any time very easily applied in everyday life. In this service activity, the result is that the respondent can increase knowledge about appropriate parenting to be given to children, how to maintain reproductive health and how to meet children's nutritional needs to how to manage stress and find out the factors that cause stress. in this case the respondent can also add skills to manage stress using relaxation techniques that can be done at home as a giver of calm and relieve stress experienced so that when stress subsides then giving good parenting to children will not be constrained.